Pendampingan Pembuatan Legalitas Usaha dengan Registrasi NIB Melalui OSS pada UMKM Wilayah Kedung Baruk.docx - Satria, Muhammad Rafi Dwi; Pudjoprastyono, Hery (Peneliti.net, 2024)
MSMEs play an important role in the course of Indonesia's economic progress, particularly in Kedung Baruk Village, where numerous micro, small, and medium enterprises (MSMEs) thrive. However, some business actors in Kedung Baruk Village still fail to comprehend the significance of possessing business legitimacy, such as a Business Identification Number (NIB). To overcome this problem, activities aimed at increasing knowledge about legality were carried out to provide assistance to MSMEs in the process of making NIB through the Online Single Submission (OSS) website. This assistance includes assistance in collecting documents, filling out forms, and understanding the procedures involved in business legality and business registration in Kedung Baruk Village.